Potential research on therapeutics application of Plantderived Extracellular Vesicles (PDEVs) in dental disease in Malaysia / Kazi Ahsan Jamil and Norhayati Liaqat Ali Khan - Ahsan Jamil, Kazi; Liaqat Ali Khan, Norhayati (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Science witnessed a dramatic growth in studies on extracellular vesicles (EVs). Similar to human, PDEVs serves as a potential tool between cells, transporting signaling molecules to mediate cellular intercellular communication in the form of nano cargoes (40-150 nm) which consist of lipid, protein, and RNA to exhibit pharmacological potential as an anti-inflammatory, antioxidant and anticancer. Moreover, PDEVs are ecofriendly, do not cause cell toxicity, and do not harbor zoonotic. More importantly, highly biocompatible, allows large-scale production. FAO/INFOODS named "FoodEVs". PDEVs easily enter mammalian cells and intermediate plant-animal cross-kingdom plays a role in the homeostatic regulation of the immune system, tissue engineering, and delivery of therapeutic molecules of various origins. This review aims to introduce the potential research opportunity on therapeutics application of plant-derived extracellular vesicles (PDEVs) in dental and oral diseases to support the New Key Economic Areas (NKEA) 2027 target in Malaysia.